Cardiovascular and renal comorbidities among saudi patients with type 2 diabetes: A cross-sectional observational study - Syed Irfan Karim; Kamran Sattar; Tauseef Ahmad; Mustafa Kamal Memon; Abdulfattah S. Alqahtani; Abdulrahman M. Alsubiheen; Fahad Abdulaziz Alrashed (PLoS ONE, 2025)
Objective This study aims to investigate the prevalence and patterns of cardiovascular and renal complications among patients with T2DM in the Saudi population and elucidate the extent of these comorbidities and their potential risk factors. Methods A cross-sectional observational study was conducted across three research locations in Riyadh, Saudi Arabia. The study incorporated the first 248 T2DM patients who met the criteria and provided their consent. The sites for this research comprised one secondary care public hospital, one public primary care clinic, and one private medical facility. Efforts were made to evenly distribute patients across the six locations, spanning three distinct sectors. Should any location fall short of its patient target, other sites would step in to balance the deficit. Patient data was gathered during their enrollment visit as well as the patient’s medical records. These encompassed variables such as age, gender, race, smoking status, residential location, duration of T2DM, most recent HbA1c, blood pressure, lipid levels, kidney function, and most recent weight/body mass index (BMI). Results Those with diabetes for five years or longer were more likely to have CKD (2.1 times higher), CAD (3.2 times higher), cerebrovascular disease (4.3 times higher), and hypertension (6.2 times higher). Most participants knew diabetes was a common health problem, and those with diabetic relatives were at a higher risk. In the present study, patients with uncontrolled HbA1C diabetes demonstrated a notably increased prevalence of various comorbidities CKD (OR=3.9, p < 0.0001), CAD (OR=2.3, p = 0.007), CHF (OR=3.1, p = 0.0001), cerebrovascular disease (OR=2.4, p = 0.0004), CVD (OR=4.2, p=<0.0001) and hypertension (OR=3.5, p = 0.0001) compared to those without uncontrolled HbA1C diabetes. However, CVD and hypertension shows a stronger association with diabetes The analysis demonstrated that diabetes was highly correlated to neuropathy (t = 2.204, p = 0.002), coronary artery disease (t = 1.53, p = 0.03), congestive heart failure (CHF) (t = 1.34, p = 0.05), cerebrovascular Disease (t = 2.65, p = 0.009), and hypertension (t = 5.05, p = 0.000). Conclusion We concluded that patients who had diabetes for five years or more had considerably greater risks of developing comorbidities such as chronic kidney disease, coronary artery disease, cerebrovascular disease, and hypertension. Among others hypertension being a major comorbidity that significantly influences the progression or presence of diabetes. This highlights the necessity of beginning treatment as early as possible and maintaining glycemic control to reduce the risk of diabetes-related problems in the long run. One limitation of this study is its cross-sectional design, which only captures data at a single point in time, preventing the establishment of causal relationships between variables.